The semiotics of consumption : interpreting symbolic consumer behavior in popular culture and works of art - Holbrook, Morris B. (Approaches to semiotics ;, 1993)
The Semiotics of Consumption: Interpreting Symbolic Consumer Behavior in Popular Culture and Works of Art (Approaches to Semiotics).